Greening parking lots to decrease stormwater runoff and improve water quality - Kerner, Natalie (My University, 2025)
As society becomes increasingly more reliant on vehicular transportation, the demand for sufficient storage, or parking lots, continues to grow. To satisfy this demand, property owners and developers commonly budget to maximize space to meet the need for parking during peak rush times. This results in a sweeping stretch of impervious paving, often with many spots left empty. The areas that may come to mind are parking areas for shopping malls and stadiums that are frequently never filled or sit vacant half of the year. The effects of these spaces are significantly damaging to the surrounding environment as they can cause high volumes of runoff and degrade the water quality that is directed downstream. However, these environmental impacts can be reduced through implementing more green infrastructure. Gray infrastructure has historically been more commonly used in directing stormwater using its structural network to quickly move water toward nearby water bodies. Alternatively, green infrastructure is a system that manages stormwater by imitating the natural water cycle. This study aims to explore the different types of green infrastructure, and how they can be implemented in parking lots to best mitigate their environmental impacts. Research into successful existing systems, stormwater runoff quality testing, and precedent studies will all inform a projective design to address stormwater management around Bill Snyder Stadium and Chester E. Peters Recreation Complex at Kansas State University.
Keywords: Green parking lots; Stormwater runoff; Green infrastructure; Stormwater quality